Sleep Quality and Insomnia Are Associated With Quality of Life in Functional Dyspepsia - Wuestenberghs, Fabien; Melchior, Chloé; Desprez, Charlotte; Leroi, Anne-Marie; Netchitailo, Marie; Gourcerol, Guillaume (Frontiers in Neuroscience, 2022)
BACKGROUND: Sleep disturbances are common in patients with functional dyspepsia. Our aim was to assess the relationship between subjective sleep and quality of life and to identify factors associated with impaired sleep in functional dyspepsia. METHODS: One thousand two hundred and twenty patients referred for functional gastrointestinal disorders at a single tertiary care center between end 2017 and June 2019 were studied using a self-administered questionnaire. 355 patients with Rome IV-based functional dyspepsia were identified. Sleep was assessed using both the Pittsburgh Sleep Quality Index (PSQI) and the Insomnia Severity Index (ISI). The severity of dyspeptic symptoms was assessed using the Total Symptom Score (TSS). Quality of life was assessed by the GastroIntestinal Quality of Life Index (GIQLI). Anxiety and depression levels were evaluated using the Hospital Anxiety and Depression (HAD) scale. KEY RESULTS: Among the 355 patients with functional dyspepsia, 66 (18.6%) patients displayed normal sleep quality whereas 289 (81.4%) patients had altered sleep quality. Functional dyspepsia patients with sleep disturbances were older (48.1 ± 15.4 vs. 41.4 ± 16.0, p = 0.0009), had decreased quality of life (GIQLI: 75.3 ± 18.5 vs. 92.1 ± 15.4, p < 0.0001), greater severity of their symptoms (TSS: 18.9 ± 3.6 vs. 17.2 ± 3.9, p = 0.0007), and higher anxiety and depression scores (HADS: 17.7 ± 7.2 vs. 11.9 ± 5.1, p < 0.0001). A correlation was found between sleep quality and quality of life (r = -0.43 [95% CI: -0.51 to -0.34], p < 0.0001). Independent factors predicting poor sleep quality were age (OR 1.03 [95% CI = 1.01-1.05], p = 0.006), depression level (OR 1.27 [95% CI = 1.16-1.39]; p < 0.0001) and the severity of dyspeptic symptoms (OR 1.13 [95% CI = 1.04-1.22]; p = 0.004). CONCLUSIONS & INFERENCES: A high prevalence of sleep disturbances was found in patients suffering from functional dyspepsia, with 81% of them having altered sleep quality and 61% having insomnia based on subjective assessment. Altered sleep quality and insomnia were associated with altered quality of life, higher severity of symptoms and higher anxiety and depression scores in this disorder.